Physical Studies of the Organization and Transcription of the Genome of Human Adenovirus Type 12 - Smiley, Richard James (My University, 1977)
The adenovirus type 12-specific RNA synthesized during productive infection of human cells and in oncogenically transformed rodent cells was studied using the techniques of nucleic acid hybridization. Before the onset of viral DNA replication during productive infection (i.e., early), RNA derived from about 30% of the viral genome was detected in the cytoplasm, while RNA complementary to at least 80% of the genome was detected in the cytoplasm after the onset of DNA replication (late). At both early and late stages of productive infection RNA complementary to a larger fraction of the viral genome was found in the nucleus than in the corresponding cytoplasm, implying the existence of sequence - specific RNA processing and/or transport mechanisms.
The segments of the viral genome encoding early and late cytoplasmic RNA were mapped using subgenomic DNA fragments generated by bacterial restriction endonucleases. A minimum of four separate regions encoding early and late cytoplasmic RNA were positioned by this method.
Two cloned lines of oncogenically transformed rodent cells were found to contain virus specific RNA mapping within the leftmost 17% of the viral genome. Both "early" and "late" classes of cytoplasmic RNA were found in both cell lines. One line contained, in addition, small amounts of RNA encoded within the extreme right hand 9% of the viral genome. The other line contained only RNA derived from the left end of the genome.
The map of the sites on the adenovirus type 12 genome expressed as early and late cytoplasmic RNA deduced during this study is similar, if not identical, to those recently obtained by other workers with the distantly related adenoviruses 2 and 5. This similarity suggests that although the DNA of adenoviruses 12 and 2 share few nucleotide sequences in common, the overall organization of the two genomes is similar.
Keywords: Biology; Biology